The South-American Situation on Globalization and Competitiveness (2015)
The objective is to elaborate a database with an analysis of each of the countries within each country, but not to compare indicators between them. Thus, the work becomes a reference of information for all those interested in consulting the situation in a given country of Latin America in terms of globalization and competitiveness in the year 2015.